Efl Learners’ Ability in Learning Speaking Skills through Digital Media - Herwanis, Delfia; Alhusna Madzlan, Noor; Zakaria, Rahmanita; Rusmiati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
English is considered a foreign language in Indonesia and is required to be studied from primary school through university. Almost all modern Islamic boarding schools require learners to speak English and Arabic on a daily basis. This paper aims to discuss how current Islamic boarding school students' speaking abilities have improved as a result of their use of digital media. The writer selected this medium based on a preliminary investigation that revealed learners' reluctance to use the English language, yet their delight in using Arabic in their daily lives. This study employed a quantitative approach, surveying 23 eighth-grade students using a 5-point Likert scale questionnaire to gather data on their experiences and self-confidence in speaking English through digital media. The use of digital media in the classroom inspires students to speak English. Many of our students continue to struggle with proper sentence construction and pronunciation in English. In other words, this study will look at how EFL students' speaking skills have gotten better because they use digital media. The results suggest that digital media has a substantial impact on students' pronunciation, vocabulary retention, sentence construction, and general confidence in speaking English. The findings suggest that incorporating digital media into English language instruction can significantly improve learners' speaking abilities when studying English as a foreign language.